Dieting changes serotonergic function in women, not men: implications for the aetiology of anorexia nervosa? - Goodwin, G; Fairburn, C; Cowen, P (1987)
The increase in plasma prolactin which follows intravenous administration of L-tryptophan (LTP) was used to assess changes in brain 5-hydroxytryptamine (5-HT) function in normal male and female subjects, following a three week period of dieting. In women, but not men, there was a marked increase in the prolactin response to LTP, suggesting that dieting had caused alterations in brain 5-HT-mediated responses. In contrast, dieting did not alter the prolactin response to thyrotropin releasing hormone in either men or women, indicating that the changes in response to LTP could not be attributed to an increase in pituitary reserve of prolactin. These findings suggest that dieting alters brain 5-HT function in women but not in men. Biological factors as well as greater psychosocial pressures to diet may contribute to the high prevalence of eating disorders amongst women.